Efficacy of combination therapy for the management regime of Alopecia areata - Chowdhury, MM; Rahman, MH; Wahab, MA (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S19-22 The abstract of this article is available on the PubMed website